The Impact of the Covid-19 Pandemic on SMEs in BRICS Economies: Current Findings and Future Research Opportunities - Frank Ranganai Matenda Matenda; Mabutho Sibanda (Ilomata International Journal of Tax and Accounting, 2024)
The COVID-19 pandemic has significantly and adversely influenced the operations of small-to-medium enterprises (SMEs) worldwide. Even though SMEs are associated with a unique traditional set of non-financial and financial challenges, the COVID-19 calamity shock has been harsh and extensive across SMEs in BRICS countries (Brazil, Russia, India, China, and South Africa), which are the fastest growing major emerging economies. This study examines the influence of the COVID-19 catastrophe on SMEs in BRICS countries and opportunities for future research. A systematic literature review is employed and twenty-six research articles are analysed to answer the research question of interest. The study results indicated that the pandemic affected innovative operational approaches of SMEs, exposed SMEs to financial challenges, influenced SME and stakeholder confidence, threatened the very survival of most SMEs, delayed the resumption of work in SMEs, and influenced market demand and supply and consumption. Further, the study results revealed that the analysis of the influence of the COVID-19 pandemic on SMEs in BRICS nations has some distinctive and uncharted areas since this research field has a reasonably short history. These findings carry significant implications for SMEs by advocating for the introduction of policy initiatives that boost capacity building and encourage work resumption in SMEs during crisis periods.